2004
DOI: 10.1111/j.0016-7398.2004.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

The Singapore River thematic zone: sustainable tourism in an urban context

Abstract: This paper explores the concept of sustainable tourism and how it applies to urban destinations such as Singapore. As tourism is an important industry in Singapore, in terms of employment, business activity and an income generator, the Singapore Tourism Board is continuously looking at potential avenues to make Singapore a competitive destination. We examine the use of thematic zones in Singapore as a strategy to achieve its ambition of becoming a tourism capital of the world. By focusing on a case study of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 10 publications
0
25
0
1
Order By: Relevance
“…The urban tourism development should, therefore, seek a more productive and harmonious relationship among visitors, host communities and the environment (Savage, Huang, Chang, 2004). Page (1995) stated that many European cities improved their centers by creating pedestrian zones, establishing parks and cycling routes, by investing in modern shopping centers and developing the city's marketing around a specific theme.…”
Section: Urban Tourismmentioning
confidence: 99%
“…The urban tourism development should, therefore, seek a more productive and harmonious relationship among visitors, host communities and the environment (Savage, Huang, Chang, 2004). Page (1995) stated that many European cities improved their centers by creating pedestrian zones, establishing parks and cycling routes, by investing in modern shopping centers and developing the city's marketing around a specific theme.…”
Section: Urban Tourismmentioning
confidence: 99%
“…This project was carried out in response to a government report, ''Tourism 21: A Vision of a Tourism Capital'', released after the Asian financial crisis of 1996. It proposed a new strategy which moved away from the previous model of producing enclosed pockets of exotic themed environments to a model that conceived of open attractions in different parts of the city (Chang, 2010;Savage et al, 2004). By overlaying onto the stream of everyday life a thematic map for touristic consumption, this model of embedded tourism conceived of exoticized local culture as lived and continuous, rather than suspended and segregated.…”
Section: Introductionmentioning
confidence: 99%
“…The notion of SUT also implies a desire to seek a more productive and harmonious relationship among visitors, host communities and the environment (Savage et al, 2004), whether natural or in urban settings. A number of characteristics of SUT have been discussed above, and based on this discussion, it has been suggested that in an urban setting both 'front room' and 'back room' sustainability be encouraged in order to move towards sustainability.…”
Section: Discussionmentioning
confidence: 99%